Vegan Diet: A Novel Trend in Healthy Living - Kamei, Gaithaongamliu; Rasane, Prasad; Singh, Jyoti; Kaur, Sawinder; Gunjal, Mahendra; Kaur, Jaspreet; Gupta, Raghav; Mahato, Dipendra K.; Gurumayum, Sushma; Dwivedi, Sunil Kumar (Current Nutrition & Food Science, 2024)
An entirely animal-free diet that prioritizes natural plant-origin foods such as vegetables, fruits, whole grains, pulses, and lentils is known as a vegan diet. Lowering persistent diseases like type-2 diabetes, cardiovascular conditions, cancer, and many others offers numerous positive health effects. Different aspects of how a vegan diet affects health are studied, and the dietary pattern is analyzed. Along with the trend of a vegan diet, many people have become aware of the importance of following a vegan diet, and many do this for health reasons or due to religious beliefs. A vegan diet has also been seen to positively affect aging. As vegan diet choices are growing, there are now more options for meat and non-dairy alternatives. Optimization for developing an alternative vegan food product is necessary to produce the most favorable product quality and achieve the best. This paper indicates the vegan diet as a whole and how the vegan diet can help treat chronic diseases. It also reviews vegan products for alternative use and their stance in the food industry.
Keywords: health benefits